1998
DOI: 10.1537/ase.106.99
|View full text |Cite
|
Sign up to set email alerts
|

Ainu and Ryukyuan Cranial Nonmetric Variation: Evidence which Disputes the Ainu-Ryukyu Common Origin Theory.

Abstract: Their trait-frequency patterns were compared with the samples from East/South eastAsia and the world using Smith's Mean Measure of Divergence (MMD) sta tistic,principal coordinate analysis, and neighbor-joining clustering algorithm. The results indicated that the Ryukyuan samples aligned with the East/South eastAsian•gMongoloid•hcluster and are far distant from the Jomon/Ainu cluster. These results do not support the prevailing view which favors a common origin of the Ainu and Ryukyuan peoples. Moreover, evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 33 publications
6
49
0
Order By: Relevance
“…Hanihara, , 1998Mizoguchi, 1986;Brace et al, 1989;Ossenberg, 1992;Yamaguchi, 1992;Ishida, 1996;Matsumura, 2001;Dodo and Kawakubo, 2002). The absence of evidence for a close affinity between any of the Ryukyu Island cranial series and the prehistoric Jomon and modern Ainu cranial series has been supported by other work in physical anthropology (Pietrusewsky, 1996;Doi et al, 1997;Omoto and Saitou, 1997;Dodo et al 1998).…”
Section: Introductionmentioning
confidence: 84%
“…Hanihara, , 1998Mizoguchi, 1986;Brace et al, 1989;Ossenberg, 1992;Yamaguchi, 1992;Ishida, 1996;Matsumura, 2001;Dodo and Kawakubo, 2002). The absence of evidence for a close affinity between any of the Ryukyu Island cranial series and the prehistoric Jomon and modern Ainu cranial series has been supported by other work in physical anthropology (Pietrusewsky, 1996;Doi et al, 1997;Omoto and Saitou, 1997;Dodo et al 1998).…”
Section: Introductionmentioning
confidence: 84%
“…The period during which the temporal change occurred in Tanegashima was compared to the period when such changes occurred on the central Japanese main island, with the aim to examine the possible causes that underlie the regional differences in the timing of temporal changes. Finally, from the results of this study, as well as by considering some recent osteological evidence (Doi et al, 1997;Doi, 1998Doi, , 2003Doi, , 2004Dodo et al, 1998Dodo et al, , 2000Asato and Doi, 1999;Matsushita, 2001), we examine the characteristics of the prehistoric population of the Nansei Islands, and discuss the validity of the 'Jomonese-Ryukyuan common origin theory' from a prehistoric perspective.…”
Section: Introductionmentioning
confidence: 77%
“…(Suda, 1950;Terakado Y., 1976;Ikeda and Tagaya, 1980), craniometry (Hsü, 1948;Ikeda, 1974;Tagaya and Ikeda, 1976;Pietrusewsky, 1994Pietrusewsky, , 1999Pietrusewsky, , 2004Doi et al, 1997;Doi, 1998Doi, , 2003Doi, , 2004Asato and Doi, 1999), cranial nonmetric traits (Mouri, 1986;Dodo, 1992;Dodo et al, 1998Dodo et al, , 2000, mitochondrial DNA (Horai et al, 1996), and the human leukocyte antigen (HLA) gene (Hatta et al, 1999;Tokunaga, 2003). Some arguments against the theory have been highlighted, particularly in the recent studies by Dodo (1992), Doi et al (1997), Doi (1998Doi ( , 2003Doi ( , 2004, Dodo et al (1998Dodo et al ( , 2000, and Asato and Doi (1999). From the viewpoint of dental morphology, Manabe et al (1999a) performed a study using dental plaster casts of modern, young, living Okinawa main islanders; their study suggested that this population was much more similar to the migrant Yayoi and modern Japanese main island populations than to the Jomonese and Hokkaido Ainu populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations